Antifibrotic drugs as treatment of nonidiopathic pulmonary fibrosis interstitial pneumonias: the time is now (?) - Kreuter, Michael; Wälscher, Julia; Behr, Jürgen (Current opinion in pulmonary medicine, 2017)
Therapeutic advances in the management of idiopathic pulmonary fibrosis (IPF) has led to improved outcomes with the use of the antifibrotic agents pirfenidone and nintedanib, with a number of randomized studies demonstrating benefits in slowing disease progression in IPF. However, treatment of other fibrosing interstitial lung diseases (ILD) remains challenging. Observational and uncontrolled studies investigating pirfenidone and nintedanib in non-IPF ILDs suggest potential benefits, although the data is weak. A number of randomized controlled trials evaluating pirfenidone and nintedanib in a variety of fibrosing ILDs are currently enrolling or planned. The review will discuss the rationale for use of established antifibrotic drugs approved for IPF for use in non-IPF ILD, describe supportive data from observational studies and ongoing clinical trials.